2014
DOI: 10.1111/dme.12644
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of latent autoimmune diabetes in adults in northern India

Abstract: In the present north-Indian population with Type 2 diabetes, the overall prevalence of GAD antibodies and the prevalence of either GAD or IA2 antibodies were considerably lower than those reported in white European populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
1
17
1
Order By: Relevance
“…Frequency of GADA positivity in our cohort was considerably higher than 1.5% and 1.6% reported in two large studies involving adult north Indian subjects The participants of these two studies had higher mean age and longer duration of diabetes than in our study [33,37]. This can be the possible explanation for the discrepancy in results as diabetes autoantibodies in the sera tend to disappear with increasing age and duration of diabetes [3,15].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Frequency of GADA positivity in our cohort was considerably higher than 1.5% and 1.6% reported in two large studies involving adult north Indian subjects The participants of these two studies had higher mean age and longer duration of diabetes than in our study [33,37]. This can be the possible explanation for the discrepancy in results as diabetes autoantibodies in the sera tend to disappear with increasing age and duration of diabetes [3,15].…”
Section: Discussioncontrasting
confidence: 80%
“…This can be the possible explanation for the discrepancy in results as diabetes autoantibodies in the sera tend to disappear with increasing age and duration of diabetes [3,15]. Moreover, sensitivity of the assay used for GADA measurement in one of these studies was lower than used in our analyses [37].…”
Section: Discussionmentioning
confidence: 70%
“…Compared to Caucasians, results of large studies have shown lower prevalence of LADA in Asian population ranging from 2.6 % in the United Arab Emirates to 5.7% in China. Two large studies on Indian subjects also revealed low prevalence of LADA 2.6% and 3.2%. There seems to be a clear difference between the prevalence of LADA in Northern Europe and Asia.…”
Section: Comparision Of Lada Between Asian and Western Populationmentioning
confidence: 99%
“…With reference to the prevalence of LADA in India, studies have revealed controversial results [36][37][38][39]44,45 Such variation in results may be attributed to the differential aspects such as age at onset, demographics of the studied subjects, and methods used to measure GAD/Protein tyrosine phosphatase-like protein (IA-2) antibodies. Considerably, high prevalence of LADA was reported in few studies.…”
Section: Epidemiologymentioning
confidence: 99%
“…Despite the high prevalence of T2D in populations of Asian ancestry, LADA prevalence when compared to populations of European ancestry has been reported to be generally lower in China, Japan, Korea and India (2.5-9.2%) ( Table 1)[48, [96][97][98][99][100][101][102]. In a study comparing a European ancestry cohort with three ethnic groups from Singapore (Indian, Malay and Chinese) [103], glutamic acid decarboxylase (GAD) autoantibodies were more frequent in the European cohort, while islet antigen 2 (IA-2) antibody positivity was higher in the Asian ethnic groups.…”
Section: Asian Ancestrymentioning
confidence: 99%